Isolation and purification of polar compounds from Eupatorium fortunei Turcz by high-speed counter-current chromatography. Issue 1 (20th January 2021) - Guo, Yuru; Chen, Yi; Zheng, Jie; Huang, Wei; Zhang, Lu; Zhang, Hui; Yan, Jizhong
Abstract: In traditional Chinese therapy, the decoction of herbal products is commonly used as a therapeutic drug, which takes water as the extraction medium and contains many hydrophilic compounds. The main compounds reported in Eupatorium fortunei Turcz were volatile oils. However, polar constituents of its decoction were less studied. In this paper, polar compounds in aqueous extract of E. fortunei Turcz were isolated by counter-current chromatography combined with a macroporous resin column. By the system of n -butanol/acetonitrile/(273 mg/mL) (NH4)2 SO4 solution (3:1:4.4, v/v/v), 205.0 mg of 10% ethanol fraction was separated to yield 2.4 mg of the trans-coumaric acid-3-O- β -D-glucoside with the purity of 95.0%. By the system of n -hexane/ethyl acetate/water (1:4:5, v/v/v), 92.0 mg of ethanol fraction was separated to yield 11.3 mg of trans- o -coumaric acid with a purity of 94.2%. Through the isolation and identification of compounds of characteristic peaks, it was effective to provide a theoretical basis for qualitative identification and quantitative determination of maker compounds in the research of quality assessment for E. fortunei Turcz. Graphical Abstract: